If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -11x = 14x Solving 40 + -11x = 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 40 + -11x + -14x = 14x + -14x Combine like terms: -11x + -14x = -25x 40 + -25x = 14x + -14x Combine like terms: 14x + -14x = 0 40 + -25x = 0 Add '-40' to each side of the equation. 40 + -40 + -25x = 0 + -40 Combine like terms: 40 + -40 = 0 0 + -25x = 0 + -40 -25x = 0 + -40 Combine like terms: 0 + -40 = -40 -25x = -40 Divide each side by '-25'. x = 1.6 Simplifying x = 1.6
| (5x-1)(2x+6)= | | 1.4q-4.3-5.2q=4.8q-3.8 | | -10(-36)=-180 | | 9t(2x)=2-(3x) | | 3/x+1=9/3 | | x+(x+30)+(2x-50)=180 | | 3.5v+8=12.5-v | | 2x+34-22= | | 9+(2x)=2-(3x) | | 15=9-3x | | 4x^2+3x+1=1-x | | 5*x^4=100 | | -2+12=5b-8-4b | | -7+4x+3=2/3(3x+9) | | 5(a+6)+4a-7=-(2a-2) | | x^2-7x+3=3-x^2+x | | 1/4(3x-16)+1/4x=5.1/3 | | 5x+13y=1 | | 35/3*7/9 | | -24-4y=24 | | 7(u+2)=84 | | 3x^2+x-3=2x^2+7-2x | | ln(x^(5/2))+ln(9x) | | 6sqrt(x-1)+3=0.04x+2.96 | | y-4=3(3+2) | | x+(-0.75)=0.5 | | -2(c-61)=-10 | | y-4=3(2+2) | | -9(7)-2= | | y-4=3(1+2) | | x+8=-22+6 | | y-4=3(0+2) |